Gut microbiota‐derived synbiotic formula (SIM01) as a novel adjuvant therapy for COVID‐19: An open‐label pilot study. Issue 5 (2nd March 2022) - Zhang, Lin; Xu, Zhilu; Mak, Joyce W Y; Chow, Kai Ming; Lui, Grace; Li, Timothy C M; Wong, Chun Kwok; Chan, Paul K S; Ching, Jessica Y L; Fujiwara, Yasuhiro; Chan, Francis K L; Ng, Siew C
Abstract: Background and Aim: Gut dysbiosis is associated with immune dysfunction and severity of COVID‐19. Whether targeting dysbiosis will improve outcomes of COVID‐19 is unknown. This study aimed to assess the effects of a novel gut microbiota‐derived synbiotic formula (SIM01) as an adjuvant therapy on immunological responses and changes in gut microbiota of hospitalized COVID‐19 patients. Methods: This was an open‐label, proof‐of‐concept study. Consecutive COVID‐19 patients admitted to an infectious disease referral center in Hong Kong were given a novel formula of Bifidobacteria strains, galactooligosaccharides, xylooligosaccharide, and resistant dextrin (SIM01). The latter was derived from metagenomic databases of COVID‐19 patients and healthy population. COVID‐19 patients who were admitted under another independent infectious disease team during the same period without receiving SIM01 acted as controls. All patients received standard treatments for COVID‐19 according to the hospital protocol. We assessed antibody response, plasma proinflammatory markers, nasopharyngeal SARS‐CoV‐2 viral load, and fecal microbiota profile from admission up to week 5. Results: Twenty‐five consecutive COVID‐19 patients received SIM01 for 28 days; 30 patients who did not receive the formula acted as controls. Significantly more patients receiving SIM01 than controls developed SARS‐CoV‐2 IgG antibody (88% vs 63.3%; P  = 0.037) by Day 16. One (4%) and 8 patients (26.7%) in the SIM01 and control group, respectively, failed to develop positive IgG antibody upon discharge. At week 5, plasma levels of interleukin (IL)‐6, monocyte chemoattractant protein‐1 (MCP‐1), macrophage colony‐stimulating factor (M‐CSF), tumor necrosis factor (TNF‐α), and IL‐1RA reduced significantly in the SIM01 but not in the control group. There was a significant negative correlation of nasopharyngeal SARS‐CoV‐2 viral load and SIM01 intervention. Metagenomic analysis showed that bacterial species in SIM01 formula were found in greater abundance leading to enrichment of commensal bacteria and suppression of opportunistic pathogens in COVID‐19 patients by week 4 and week 5. Conclusions: This proof‐of‐concept study suggested that the use of a novel gut microbiota‐derived synbiotic formula, SIM01, hastened antibody formation against SARS‐CoV‐2, reduced nasopharyngeal viral load, reduced pro‐inflammatory immune markers, and restored gut dysbiosis in hospitalised COVID‐19 patients.